1983
DOI: 10.1002/eji.1830131110
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer activity in (C57BL/6 × DBA/2)F1 hybrids undergoing acute and chronic graft‐vs.‐host reaction

Abstract: The present findings demonstrate that a total i.v. transfer of 100 X 10(6) C57BL/6 (B6) parental spleen cells into untreated (C57BL/6 X DBA/2)F1 hybrids (B6D2F1) resulted in acute runting, which was associated with a significantly elevated graft-vs.-host (GVH) index over a one-month period following GVH induction. Furthermore, this B6-induced acute GVH disease was associated with a marked depression of natural killer (NK) cell activity (spleen and peripheral blood) (with or without addition of mouse fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Pattengale and coworkers were the first to demonstrate in murine models that acute but not chronic GvHD induce a marked decrease in NK cell activity associated with an impaired production of IFN-γ (80). NK cell reconstitution appears to be significantly delayed by acute GvHD in mice (81) and by acute and chronic GvHD in humans (42, 8285).…”
Section: Gvhd Modulation Of Nk Cellsmentioning
confidence: 99%
“…Pattengale and coworkers were the first to demonstrate in murine models that acute but not chronic GvHD induce a marked decrease in NK cell activity associated with an impaired production of IFN-γ (80). NK cell reconstitution appears to be significantly delayed by acute GvHD in mice (81) and by acute and chronic GvHD in humans (42, 8285).…”
Section: Gvhd Modulation Of Nk Cellsmentioning
confidence: 99%
“…We confirmed that IL-2 administration to non-transplanted normal mice increased NK cells in an IL-2 dose-dependent manner, however, IL-2 administration to allo-transplanted recipient mice did not increase NK cells in the experimental HSCT used in this study ( Supplemental Figure S4 ). In fact, previous studies have shown that more than 50 million spleen cells need to be infused at transplant in order to observe NK cells in the B6-into-B6D2F1 system ( 42 , 43 ). In our experimental setting, we infused 5 million spleen cells and it appears to be not enough to evaluate NK cells after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…These findings thus extend earlier observations by providing a mechanism for the augmented NK activity demonstrated in GVH reaction [3., 20,29,33]. In these studies, unirradiated F, hybrid mice were used as hosts for the GVH reaction, and we proposed that an F| response to the injected parental cells might be one stimulus lor the activation of NK cells |3|, F, miee recognize and reject haemopoietic cells from certain parental strains [6,8], and it is probable that host NK cells mediate this resistance |8, 14,21.44].…”
Section: Discussionmentioning
confidence: 99%